Isolating membrane, preparation method thereof and battery

By using polymers such as polypropylene, polyethylene, and inorganic ceramic materials such as alumina and boehmite in the diaphragm, an efficient ceramic composite diaphragm is formed, which solves the problem of powder loss and insufficient tensile strength of the ceramic coated diaphragm. Higher mechanical strength and electrochemical properties are achieved while reducing production costs.

CN119153892APending Publication Date: 2024-12-17JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD

Patent Information

Application Number
CN202411116646.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing ceramic-coated diaphragms are prone to powder loss during long-term use, and the tensile strength is reduced, making it difficult to take into account both cost and mechanical strength.

Method used

Using a separator film formulation including polypropylene, polyethylene, alumina, boehmite, polystyrene, thickener, dispersant, plasticizer and nanooxide, a homogeneous slurry is formed by melting, stirring and shearing treatment. Apply directly to the base film to avoid the reprocessing step of spraying the coating.

Benefits of technology

It improves the thermal stability, puncture resistance and electrolyte wetting properties of the diaphragm, reduces production costs and time, avoids the risk of powder loss, and has higher hardness and better uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004993903310000171
    Figure BDA0004993903310000171
  • Figure BDA0004993903310000181
    Figure BDA0004993903310000181
  • Figure BDA0004993903310000191
    Figure BDA0004993903310000191
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to an isolating membrane, a preparation method thereof and a battery. The isolating membrane comprises the following components: a first polymer, a second polymer, an inorganic ceramic material, a thickening agent, a dispersing agent, a plasticizer, a surfactant and a nano oxide, wherein the first polymer comprises polypropylene and / or polyethylene; the second polymer includes polystyrene. The preparation method of the isolating membrane comprises the following steps: mixing a first polymer, a second polymer, an inorganic ceramic material, a thickening agent, a dispersing agent, a plasticizer, a surfactant and a nano oxide to obtain a mixture; sequentially melting, stirring and shearing the mixture to obtain slurry; and coating a substrate with the slurry, drying, and separating the substrate to obtain the isolating membrane. The risk of powder falling of the isolating membrane in long-term use can be reduced, and the physical performance and the electrochemical performance of the isolating membrane can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an isolation film and a preparation method thereof, and a battery. Background Art

[0002] The diaphragm (also called the isolation membrane) is one of the key inner components with the most technical barriers in the battery (such as lithium battery) industry chain. In order to improve the diaphragm's resistance to high temperature and heat shrinkage, enhance the diaphragm's mechanical strength, and thus improve the safety performance of the battery, a ceramic layer can be coated on the surface of the diaphragm's base film, and the good thermal stability and mechanical strength of the ceramic material can be used to improve the safety performance of the lithium-ion battery diaphragm. In addition, the ceramic layer generally has a rich pore structure and good electrolyte wettability, which can enhance the diaphragm's ability to absorb and retain liquid, thereby helping to increase the battery's service life. In addition, the ceramic layer mostly uses non-polar oxides, which can neutralize a small amount of hydrofluoric acid in the electrolyte and play a role in inhibiting battery cell flatulence.

[0003] In the related art, the method usually adopted for preparing a diaphragm with a ceramic layer is to coat the prepared ceramic slurry on a base film (such as polypropylene or polyethylene, etc.) or a multi-layer composite diaphragm base film through a coating process. After coating, the ceramic layer and the base film are tightly bonded together. However, the ceramic coated diaphragms currently used in large quantities not only reduce the tensile strength of the diaphragm, but more importantly, there is a risk of powder loss during a long service life. Therefore, how to reasonably optimize diaphragm materials such as ceramic materials and binders to prepare a diaphragm with ceramic materials having uniform thickness and reasonable pore structure, while taking into account cost and reliability of engineering applications, has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a separator and a preparation method thereof and a battery, which can reduce the risk of powder loss of the separator during long-term use and help improve the physical and electrochemical properties of the separator.

[0005] In order to solve the above technical problems, this application is implemented as follows:

[0006] According to one aspect of the present application, an embodiment of the present application provides an isolation film, wherein the isolation film comprises the following components:

[0007] A first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and nano-oxides;

[0008] Wherein, the first polymer comprises polypropylene and / or polyethylene;

[0009] The second polymer includes polystyrene.

[0010] In addition, the isolation film according to the present application may also have the following additional technical features:

[0011] In some embodiments, the isolation film includes the following components in parts by weight:

[0012] 40-50 parts of the first polymer, 2-5 parts of the second polymer, 20-30 parts of the inorganic ceramic material, 5-6 parts of the nano oxide, 1-2 parts of the thickener, 1-3 parts of the dispersant, 2-4 parts of the plasticizer and 1-3 parts of the surfactant.

[0013] In some embodiments, the thickening agent includes polyethylene glycol and / or carboxymethyl cellulose.

[0014] In some embodiments, the inorganic ceramic material includes alumina and boehmite.

[0015] In some embodiments, the mass ratio of alumina to boehmite is 1:(0.5-3).

[0016] In some embodiments, the dispersant includes a polyacrylate ammonium salt dispersant or a modified polyacrylate ammonium salt dispersant.

[0017] In some embodiments, the plasticizer includes a phthalate compound, and the phthalate compound includes at least one of DBP, BBP, DEHP, DNOP, DIDP or DINP.

[0018] In some embodiments, the surfactant includes at least one of sodium polyoxyethylene fatty alcohol ether sulfate, polyoxyethylene fatty acid ester, dodecyl methyl betaine, sodium dodecyl benzene sulfonate or sodium dodecyl sulfate.

[0019] In some embodiments, the nano-oxide includes at least one of nano-silicon oxide, nano-zinc oxide or nano-titanium oxide.

[0020] In some embodiments, the isolation membrane further includes a pore former, and the pore former includes white oil.

[0021] In some of the embodiments, the mass fraction of the pore former is 0.01 to 1 part;

[0022] In some embodiments, the isolation film further includes an antioxidant, and the antioxidant includes 2,6-di-tert-butyl-p-cresol.

[0023] In some embodiments, the antioxidant is present in an amount of 0.01 to 1 part by weight.

[0024] In some embodiments, the isolation film has a thickness of 5 μm to 35 μm.

[0025] According to another aspect of the present application, an embodiment of the present application provides a method for preparing an isolation film, the method comprising the following steps:

[0026] Mixing a first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and a nano-oxide to obtain a mixture; wherein the first polymer includes polypropylene and / or polyethylene; and the second polymer includes polystyrene;

[0027] The mixture is sequentially melted, stirred and sheared to obtain a slurry;

[0028] The slurry is coated on a substrate, dried, and separated from the substrate to obtain the isolation film.

[0029] In some embodiments, the melting temperature is 300° C. to 400° C., and the melting time is 1 h to 2 h.

[0030] In some embodiments, the stirring time is 2 h to 3 h.

[0031] In some embodiments, the shearing speed is 1000-14000 rpm, and the shearing time is 4h-5h.

[0032] In some embodiments, the viscosity of the slurry is 1200-1500 mPa.s.

[0033] In some embodiments, the coating is performed using a coating machine, and the speed regulator frequency of the coating machine is set to 20 to 40 Hz.

[0034] In some embodiments, the drying temperature is 70°C to 90°C.

[0035] In some embodiments, the isolation film has a thickness of 25 μm to 35 μm.

[0036] In some embodiments, the mixture further includes a pore former.

[0037] In some embodiments, the mixture further includes an antioxidant.

[0038] According to another aspect of the present application, an embodiment of the present application provides a battery, wherein the battery includes the aforementioned isolation membrane or the isolation membrane prepared according to the aforementioned method.

[0039] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0040] In the embodiment of the present application, the isolation membrane provided includes a first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and a nano-oxide, wherein the first polymer includes polypropylene and / or polyethylene, and the second polymer includes polystyrene. The first polymer can be used as the base film material of the isolation membrane, and the second polymer uses polystyrene to enhance the hardness, wettability and other properties of the isolation membrane; the inorganic ceramic material has good thermal stability and mechanical strength, which can be used to enhance the high temperature resistance and heat shrinkage resistance of the isolation membrane, and can also be used to enhance the mechanical strength of the isolation membrane, and has good electrolyte wettability; the addition of the thickener can be used to enhance the toughness of the isolation membrane; the addition of the dispersant can be used to further improve the high temperature resistance and mechanical strength of the isolation membrane; the addition of the plasticizer can be used to lubricate and bridge the powder particles, which is beneficial to the dispersion and stability of the slurry; the surfactant can play a good role in decontamination, emulsification, foaming and hard water resistance; the addition of the nano-oxide can play a role in improving the mechanical strength of the isolation membrane. Thus, through the synergistic effect of the above-mentioned first polymer, second polymer, inorganic ceramic material, thickener, dispersant, plasticizer, surfactant and nano-oxide, the prepared isolation membrane can have good physical and electrochemical properties, such as good thermal stability, puncture resistance and excellent wettability to electrolyte.

[0041] Compared with the existing preparation method of coating a ceramic coating on a base film, the preparation of the isolation membrane of the present invention only requires mixing the raw materials and performing a one-time processing to make the prepared isolation membrane have good thermal stability and excellent wettability to the electrolyte. There is no need for reprocessing such as spraying a coating on the surface, which saves production costs and time. Moreover, the prepared isolation membrane has better uniformity than the isolation membrane sprayed with a ceramic layer and is not prone to powdering, which can alleviate the risk of powdering of the isolation membrane prepared by the existing method during long-term use. In addition, the diaphragm has higher hardness and stronger puncture resistance, and has good application prospects.

[0042] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0043] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0048] Generally, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet and mainly plays the role of preventing the positive and negative electrodes from short-circuiting. It can also allow active ions to pass freely to form a loop. With the application and promotion of secondary batteries, people have higher and higher requirements for the performance of secondary batteries. By optimizing the separator and other components in the battery, it is helpful to further optimize the relevant performance of the battery. In the related art, a separator is prepared by coating a ceramic coating on the surface of a base film, so as to improve the mechanical strength, thermal stability, electrolyte wettability and other properties of the separator by using the ceramic coating. However, on the one hand, the existing preparation method of coating the ceramic coating on the base film by coating not only reduces the tensile strength of the separator, but also has the risk of powder falling in a long service life; on the other hand, the components of the existing separator with a ceramic coating still have more or less shortcomings, such as thermal stability, mechanical strength, etc., which need to be further improved.

[0049] In view of this, the inventors of this application have prepared a ceramic material-containing isolation membrane with uniform thickness and reduced risk of powder loss by reasonably optimizing the ceramic material and other components of the isolation membrane. The isolation membrane has good physical and electrochemical properties while taking into account the cost and reliability of engineering applications. The specific technical solution is shown below.

[0050] [Isolation film]

[0051] In some embodiments, the present application provides an isolation film, which includes the following components:

[0052] A first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and nano-oxides;

[0053] wherein the first polymer comprises polypropylene and / or polyethylene;

[0054] The second polymer includes polystyrene.

[0055] In the present application, the provided isolation membrane may also be referred to as a ceramic composite isolation membrane, which can be used to isolate the positive electrode sheet and the negative electrode sheet of a battery (such as a lithium battery).

[0056] The isolation membrane is mainly prepared from a first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and a nano-oxide, that is, the raw materials for preparing the isolation membrane mainly include the first polymer, the second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and a nano-oxide. Among them, the first polymer is the main material of the isolation membrane, that is, the first polymer is the base film material of the isolation membrane, and the first polymer can be polypropylene (PP), or can be polyethylene (PE), or can be a combination of polypropylene and polyethylene. The second polymer is preferably polystyrene (PS), such as polystyrene (PS) plastic. By blending the above-mentioned first polymer and the second polymer as the base material, it can be used to enhance the hardness, insulation, thermal insulation, wettability and other properties of the base material.

[0057] In the present application, in the separator provided, the first polymer, the second polymer, the inorganic ceramic material, the thickener, the dispersant, the plasticizer, the surfactant and the nano-oxide play a synergistic role, and synergistically improve the physical properties and electrochemical properties of the separator, especially improve the thermal stability, puncture resistance and wettability of the separator to the electrolyte, thereby improving the cycle performance and safety performance of the battery using the separator. In detail:

[0058] The first polymer can be used as the base film material of the isolation film, and the second polymer can be polystyrene to enhance the hardness, wettability and other properties of the isolation film. In particular, by blending the first polymer and the second polymer as the base material, it can be used to enhance the hardness, insulation, thermal insulation, wettability and other properties of the base material. Inorganic ceramic materials have good thermal stability and mechanical strength, and can be used to enhance the high temperature resistance and heat shrinkage resistance of the isolation film. It can also be used to enhance the mechanical strength of the isolation film and has good electrolyte wettability; in addition, by using the above thickeners, dispersants, plasticizers, surfactants, etc. in combination with inorganic ceramic materials, the binding ability of inorganic ceramic materials and thickeners can be enhanced, and their combined action can obtain a more uniform slurry, which is beneficial to improve the uniformity and heat resistance of the isolation film. The addition of thickener can be used to enhance the toughness of the isolation membrane; the addition of dispersant can be used to further improve the high temperature resistance and mechanical strength of the isolation membrane; the addition of plasticizer can be used to lubricate and bridge the powder particles, which is beneficial to the dispersion and stability of the slurry; surfactants can play a good role in cleaning, emulsification, foaming and hard water resistance; the addition of nano oxides can improve the mechanical strength of the isolation membrane; in addition, nano oxides have good thermal stability and heat dissipation performance, which can play a certain role in reducing the thermal shrinkage performance of the isolation membrane and also help to improve the tensile strength of the isolation membrane. Therefore, through the synergistic effect of the above-mentioned first polymer, second polymer, inorganic ceramic material, thickener, dispersant, plasticizer, surfactant and nano oxide, the isolation membrane prepared can have good physical and electrochemical properties, such as good thermal stability, puncture resistance and excellent wettability to electrolyte.

[0059] It should be noted that the present invention does not limit the sources of the components in the isolation membrane, such as the first polymer, the second polymer, the inorganic ceramic material, the thickener, the dispersant, the plasticizer, the surfactant and the nano-oxide, and they can be prepared by themselves or purchased from the market.

[0060] In some embodiments, the isolation film includes the following components in parts by weight:

[0061] 40-50 parts of the first polymer, 2-5 parts of the second polymer, 20-30 parts of the inorganic ceramic material, 5-6 parts of the nano oxide, 1-2 parts of the thickener, 1-3 parts of the dispersant, 2-4 parts of the plasticizer and 1-3 parts of the surfactant.

[0062] In order to achieve better coordination of the components in the isolation membrane, it has better physical and electrochemical properties. The isolation membrane material includes 40 to 50 parts of the first polymer by mass, and typical but non-limiting examples include 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, and any value in the range formed by any two of these point values. The first polymer, as the base film material of the isolation membrane, generally accounts for about 40% to 50% of the isolation membrane. If the content of the first polymer is too low, the basic function of the isolation membrane is difficult to achieve. If the content of the first polymer is too high, the content of the remaining components will be reduced, and the effect of improving the thermal stability, mechanical strength, electrolyte wettability and other properties of the isolation membrane will not be obvious.

[0063] In the present application, the first polymer can be a conventional polymer base film material in the art, such as one or more of PP, PE, etc.; as an example, when the first polymer is PP, the melting point of PP is 164-170°C, softens at about 155°C, has a molecular weight of about 80,000-150,000, and has chemical resistance, heat resistance, electrical insulation, high strength mechanical properties and good high wear resistance processing performance. Similarly, PE also has similar properties.

[0064] The isolation film includes 2 to 5 parts of the second polymer by weight, and typically but not limitingly, it can be 2 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, and any value in the range formed by any two of these point values. By blending the second polymer and the above-mentioned first polymer as a base material, it can be used to enhance the hardness, insulation, thermal insulation, wettability and other properties of the base material. If the content of the second polymer is too low, the improvement of the wettability, hardness and other properties of the isolation film is not obvious. If the content of the second polymer is too high, it may affect other properties of the isolation film and increase the cost of raw materials.

[0065] In the present application, the second polymer may be polystyrene, such as polystyrene (PS) plastic. PS is a colorless and transparent thermoplastic with a glass transition temperature higher than 100°C and excellent thermal insulation, insulation and transparency. The hardness of the separator can be increased by adding PS. In addition, PS is heated to allow the polystyrene containing a foaming agent to expand freely in a molten state, forming a small-diameter, uniformly distributed open-pore structure, which can be used to increase the wettability of the separator and improve the electrolyte wettability of the separator.

[0066] The isolation membrane includes 20 to 30 parts of inorganic ceramic material by weight, and typical but non-limiting examples include 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 30 parts, and any value in the range formed by any two of these point values. Inorganic ceramic materials are the key to improving the thermal stability, mechanical strength and electrolyte wettability of the isolation membrane, and generally account for about 20% to 30% of the isolation membrane. If the content of inorganic ceramic materials is too low, the improvement of the thermal stability, mechanical strength and electrolyte wettability of the isolation membrane is not obvious. If the content of inorganic ceramic materials is too high, it may affect other properties of the isolation membrane and increase the cost of raw materials. Therefore, by making the addition amount of inorganic ceramic materials 20 to 30 parts, the comprehensive properties of the isolation membrane such as thermal stability, mechanical strength, and electrolyte wettability can be improved while ensuring the basic functions of the isolation membrane, thereby reducing costs.

[0067] In some embodiments, the inorganic ceramic material includes alumina and boehmite.

[0068] In the present application, a composite of alumina and boehmite is used as an inorganic ceramic material. Compared with the method of using alumina alone or boehmite alone, the combination of alumina and boehmite is more conducive to improving the physical and electrochemical properties of the isolation membrane.

[0069] In some embodiments, the mass ratio of alumina to boehmite is 1:(0.5-3). Preferably, in some embodiments, the mass ratio of alumina to boehmite is 1:(1-1.5). As an example, the mass ratio of alumina to boehmite can be 1:0.5, 1:1, 1:1.5, 1:2, 1:3, etc. By controlling the mass ratio of alumina to boehmite within the above range, the porosity of the isolation membrane can be within a suitable range. If the proportion of boehmite is too high, the porosity of the isolation membrane will decrease, and the isolation membrane can also have good physical and electrochemical properties.

[0070] The isolation film includes 5 to 6 parts of nano oxide by mass, and typically but not limitedly, it can be 5 parts, 5.1 parts, 5.3 parts, 5.4 parts, 5.5 parts, 5.6 parts, 5.8 parts, 6 parts, and any value in the range formed by any two of these point values. If the content of nano oxide is too low, the improvement of the mechanical strength or hardness of the isolation film is not obvious. If the content of nano oxide is too high, it may affect other properties of the isolation film and increase the cost of raw materials.

[0071] In some embodiments, the nano-oxide includes any one of nano-silicon oxide, nano-zinc oxide or nano-titanium oxide, or a combination of at least two thereof. For the sake of brevity, the combinations within the above range are not listed one by one. The heating of the inorganic nano-oxide additives such as nano-silicon oxide, nano-zinc oxide, nano-titanium oxide, etc. can be used to improve the mechanical strength of the isolation film.

[0072] Preferably, in the present application, the nano oxide is selected from nano silicon oxide (nano SiO2).

[0073] Although the addition of can be used to improve the mechanical strength of the isolation membrane, nano oxides such as nano SiO2 are prone to agglomeration during preparation and use, blocking the pore size of the membrane and reducing its air permeability and porosity. The inventors of the present application have found that by introducing the above-mentioned second polymer, that is, polystyrene (PS), and using PS and nano SiO2 in combination, the agglomeration of nano SiO2 can be prevented and the hardness of the isolation membrane can be enhanced.

[0074] Therefore, the present invention uses PS and nano-oxides such as nano-SiO2 in combination, which can not only effectively improve the mechanical strength of the isolation membrane and avoid the agglomeration of the nano-oxides, but also enhance the hardness of the isolation membrane.

[0075] The isolation film includes 1 to 2 parts of thickener by weight, and typical but non-limiting examples include 1 part, 1.1 parts, 1.2 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 2 parts, and any value in the range formed by any two of these points. If the amount of thickener added is too little, the toughness of the isolation film is difficult to ensure, and if the amount of thickener added is too much, the main active ingredient is too low, the cost is increased, and the functions such as thermal stability and mechanical strength are difficult to achieve.

[0076] In some embodiments, the thickener includes polyethylene glycol (PEG) and / or carboxymethyl cellulose (CMC). That is, the thickener can be polyethylene glycol, can be carboxymethyl cellulose, or can be a combination of polyethylene glycol and carboxymethyl cellulose.

[0077] Preferably, in the present application, the thickener is selected from CMC.

[0078] In this application, the isolation film can be made tougher by adding thickeners such as CMC. Among them, thickeners such as CMC are not only easily soluble in cold water or hot water to form a transparent solution with a certain viscosity, but also soluble in 60% ethanol or acetone solution; in addition, they also have certain hygroscopicity and light and heat stability, which is conducive to improving the toughness of the isolation film.

[0079] The isolation film includes 1 to 3 parts of dispersant by weight, and typical but non-limiting examples include 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, and any value in the range formed by any two of these point values. If the amount of dispersant added is too little, the uniform dispersion of the system will be reduced. If the amount of dispersant added is too much, the main active ingredient is too low, the cost is increased, and the functions such as thermal stability and mechanical strength are difficult to achieve.

[0080] In some embodiments, the dispersant includes a polyacrylate ammonium salt dispersant or a modified polyacrylate ammonium salt dispersant.

[0081] Optionally, the dispersant is selected from ammonium polyacrylate.

[0082] In the present application, the dispersant may be selected from dispersants of polyacrylate ammonium salts such as ammonium polyacrylate, or may be selected from modified polyacrylate ammonium salts. As an example, ammonium polyacrylate is a low molecular weight polyacrylate ammonium salt dispersant, and ammonium salt dispersants are generally used in high solid phase dispersion systems; polyacrylate ammonium salt dispersants have excellent rheological controllability within a wide range of pH values ​​and temperatures. In addition, ammonium polyacrylate can react with alumina to improve the high temperature resistance and mechanical strength of the isolation membrane.

[0083] It should be understood that since ammonium polyacrylate can react with aluminum oxide, the final isolation membrane will contain aluminum hydroxide and polymer, the products of the reaction between the two, which can be used to improve the high temperature resistance and mechanical strength of the isolation membrane.

[0084] The isolation film includes 2 to 4 parts of plasticizer by weight, and typical but non-limiting examples include 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, and any value in the range formed by any two of these point values. If the amount of plasticizer added is too little, the dispersion stability of the slurry will be reduced. If the amount of dispersibility added is too much, the main effective component is too low, the cost is increased, and the functions such as thermal stability and mechanical strength are difficult to achieve.

[0085] In some embodiments, the plasticizer includes but is not limited to phthalate compounds, and the phthalate compounds include, but are not limited to, any one or a combination of at least two of dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), dioctyl phthalate (DEHP), di-n-octyl phthalate (DNOP), diisodecyl phthalate (DIDP) or diisononyl phthalate (DINP). For the sake of brevity, the combinations within the above range are no longer listed one by one.

[0086] Preferably, in the present application, the plasticizer is selected from DBP.

[0087] In the present application, the DBP plasticizer plays a lubricating and bridging role on the powder particles, which is beneficial to the dispersion and stability of the slurry. It is insoluble in water, but easily soluble in organic solvents such as alcohol, ether, acetone and benzene, and has a melting point of -35°C.

[0088] The isolation film includes 1 to 3 parts of surfactant by mass, and typical but non-limiting examples include 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, and any value in the range formed by any two of these point values.

[0089] In some embodiments, the surfactant includes, but is not limited to, any one or a combination of at least two of fatty alcohol polyoxyethylene ether sulfate, polyoxyethylene fatty acid ester, dodecyl methyl betaine, sodium dodecyl benzene sulfonate or sodium dodecyl sulfate. For the sake of brevity, the combinations within the above range are no longer listed one by one.

[0090] Preferably, in the present application, the surfactant is selected from sodium fatty alcohol polyoxyethylene ether sulfate (AES). AES is easily soluble in water and has excellent cleaning, emulsification, foaming and hard water resistance properties, and is an excellent surfactant.

[0091] The formula of the isolation membrane of this embodiment is mainly composed of nine parts, namely, the first polymer, the second polymer, the inorganic ceramic material, the thickener, the dispersant, the plasticizer, the surfactant and the nano-oxide. According to different goals and uses, the amount and type of each component are also different. The isolation membrane can adjust the type and ratio of each raw material component, cooperate with other components, and make each component within the above range, so that the isolation membrane has good physical and electrochemical properties, and stable performance, which can effectively alleviate the poor performance of existing isolation membranes such as thermal stability or mechanical strength.

[0092] In some embodiments, the isolation film includes the following components, measured by mass: 40 to 45 parts of a first polymer, 2 to 4 parts of a second polymer, 25 to 30 parts of an inorganic ceramic material, 5 to 5.5 parts of a nano-oxide, 1 to 1.5 parts of a thickener, 1.5 to 2.5 parts of a dispersant, 2.5 to 3.5 parts of a plasticizer, and 1.5 to 2.5 parts of a surfactant.

[0093] By rationally adjusting and optimizing the content of each component in the isolation membrane, the synergistic effect of the components can be fully utilized to further improve the physical properties, electrochemical properties or comprehensive properties of the isolation membrane, while reducing the production cost of the isolation membrane.

[0094] In some embodiments, the isolation film further includes a pore former, and the pore former includes white oil.

[0095] In some embodiments, the mass fraction of the pore former is 0.01 to 1 part.

[0096] In some embodiments, the isolation film further includes an antioxidant, and the antioxidant includes 2,6-di-tert-butyl-p-cresol.

[0097] In some embodiments, the weight percentage of the antioxidant is 0.01 to 1 part.

[0098] In some cases, in order to further improve the pore structure of the isolation membrane or improve the oxidation resistance of the isolation membrane, a certain amount of pore former and antioxidant may be added to the isolation membrane, wherein the pore former may be white oil, and the antioxidant may be 2,6-di-tert-butyl-p-cresol.

[0099] As an example, the isolation film includes the following components, measured by mass: 40-50 parts of a first polymer, 3-5 parts of a second polymer, 20-30 parts of an inorganic ceramic material, 5-6 parts of nano oxides, 1-2 parts of a thickener, 1-3 parts of a dispersant, 2-4 parts of a plasticizer, 1-3 parts of a surfactant, 0.01-1 parts of a pore-forming agent and 0.01-1 parts of an antioxidant.

[0100] It should be understood that in the present application, the pore former and the antioxidant are optional components, that is, the pore former and the antioxidant may be added to the isolation membrane, or the pore former and the antioxidant may not be added, and the specific selection and setting can be made according to actual needs.

[0101] In some embodiments, the thickness of the isolation membrane is 5μm to 35μm. In some embodiments, the thickness of the isolation membrane is 10μm to 30μm. Exemplarily, the thickness of the isolation membrane can be any point value of 5μm, 6μm, 8μm, 10μm, 12μm, 15μm, 20μm, 25μm, 30μm, 35μm, or a range value between any two. If the thickness of the isolation membrane is too thick, it may increase the internal resistance of the battery and reduce the cycle performance of the battery; if the thickness of the isolation membrane is too thin, its strength will be reduced. Therefore, the embodiment of the present application helps to ensure the mechanical strength of the isolation membrane, reduce the internal resistance of the battery, and improve the cycle performance of the battery by controlling the thickness of the isolation membrane within the above range.

[0102] [Method for preparing isolation film]

[0103] In some embodiments, a method for preparing an isolation film is provided, the method comprising the following steps:

[0104] Mixing a first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and nano-oxide to obtain a mixture; wherein the first polymer includes polypropylene and / or polyethylene; and the second polymer includes polystyrene;

[0105] The mixture is sequentially melted, stirred and sheared to obtain a slurry;

[0106] The slurry is coated on a substrate, dried, and separated from the substrate to obtain an isolation film.

[0107] In this application, by directly adding inorganic ceramic powder into the production process of the base film, there is no need to use a spray coating process, which can avoid the process of reprocessing the diaphragm, improve production efficiency and save costs. At the same time, by directly hot-melting the ceramic slurry into the base film material, the effect can be more uniform than spraying, and the functional effect can be better exerted. In addition, the phenomenon of ceramic powder falling off after spraying can be avoided, thereby improving the application effect or service life of the isolation membrane.

[0108] It should be understood that all the features and advantages described above for the “isolation membrane” are also applicable to the “method for preparing the isolation membrane” and will not be described in detail here.

[0109] In some specific embodiments, the method for preparing the isolation membrane mainly includes the following steps:

[0110] S10. preparing a mixture.

[0111] In step S10, the first polymer, the second polymer, the inorganic ceramic material, the thickener, the dispersant, the plasticizer, the surfactant, the nano-oxide, the optional pore-forming agent and the optional antioxidant are mixed to obtain a mixture; wherein the pore-forming agent and the antioxidant can be selectively added or not added according to actual needs.

[0112] Optionally, in step S10, the first polymer, the second polymer, the inorganic ceramic material, the thickener, the dispersant, the plasticizer, the surfactant, the nano-oxide, the optional pore-forming agent, the optional antioxidant, the solvent and water (such as deionized water) are mixed in a certain proportion to obtain a mixture slurry.

[0113] Optionally, the solvent may be an organic solvent such as acetone, xylene, etc. Preferably, the solvent is selected from acetone.

[0114] S20, preparing slurry.

[0115] In step S20, the mixture (mixture slurry) obtained in step S10 is melted, then stirred, and then sheared to obtain slurry.

[0116] Optionally, the melting temperature is 300°C to 400°C, and the melting time is 1h to 2h. As an example, the melting temperature may be 300°C, 320°C, 350°C, 360°C, 380°C, 400°C, etc.; the melting time may be 1h, 1.2h, 1.5h, 1.8h, 2h, etc.

[0117] Optionally, the molten material is stirred with a stirrer for 2 to 3 hours; the components in the slurry can be mixed evenly by stirring. As an example, the stirring time can be 2 hours, 2.2 hours, 2.5 hours, 2.8 hours, 3 hours, etc.

[0118] Optionally, the shearing speed is 1000-14000rpm, and the shearing time is 4h-5h. For example, a high shear emulsifier can be used for shearing, and the slurry can reach the desired viscosity by shearing. As an example, the shearing speed can be 1000rpm, 2000rpm, 3000rpm, 5000rpm, 8000rpm, 10000rpm, 14000rpm, etc., and the shearing time can be 4h, 4.2h, 4.5h, 4.8h, 5h, etc.

[0119] Optionally, the viscosity of the prepared slurry is 1200-1500 mPa.s. As an example, the viscosity of the slurry can be 1200 mPa.s, 1300 mPa.s, 1400 mPa.s, 1500 mPa.s, etc.

[0120] In the present application, by controlling the viscosity of the slurry within the range of 1200-1500 mPa.s, the uniformity of the prepared isolation membrane can be ensured, and the preparation efficiency and effect can be improved. If the viscosity of the slurry is too low, it is difficult to form a uniform and continuous film when coated on the coating machine, and it is easy to break. If the viscosity of the slurry is too high, the thickness of the cast film will be thick, and the pores of the diaphragm will be blocked.

[0121] S30, coating, drying and separating the slurry from the substrate to obtain an isolation film.

[0122] In step S30, the slurry obtained in step S20 is placed on a coating machine (such as a small coating machine), and a diaphragm matrix with a thickness of 25 μm to 35 μm is cast on a substrate (such as a glass sheet).

[0123] Optionally, the coating is performed using a coating machine, and the speed regulator frequency of the coating machine is set to 20-40 Hz, for example, the frequency may be 20 Hz, 30 Hz, 40 Hz, etc.

[0124] Then, the cast diaphragm substrate is placed in a small coating machine drying chamber for drying. Optionally, the drying temperature is 70°C to 90°C, and the drying temperature may be, for example, 70°C, 75°C, 80°C, 85°C, 90°C, etc.

[0125] After drying, the substrate is separated to prepare an isolation film.

[0126] In some embodiments, the thickness of the prepared isolation film is 25 μm to 35 μm.

[0127] Therefore, the method for manufacturing the isolation membrane provided by the present invention can enable the prepared isolation membrane to have good thermal stability and excellent wettability to the electrolyte through only one processing, and does not require reprocessing such as spraying a coating on the surface, which can save production costs and time. Moreover, the prepared diaphragm has better uniformity than the diaphragm sprayed with a ceramic layer, is not easy to fall off, has higher hardness, and is more puncture-resistant.

[0128] [Battery]

[0129] In the embodiment of the present application, the battery may be a secondary battery or a primary battery, preferably a secondary battery. For example, the battery may be a lithium-ion secondary battery, a lithium primary battery, a sodium-ion battery, a magnesium-ion battery, etc., but is not limited thereto. The battery structure of the present application includes but is not limited to a soft-pack lithium-ion battery, a square hard-shell battery, or a cylindrical hard-shell battery, etc.

[0130] It should be noted that, in the specific implementation manner, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the battery of the present application is not limited to a lithium-ion battery.

[0131] In some embodiments, a provided battery includes the separator provided by any of the above embodiments.

[0132] In the present application, the isolation membrane provided has good thermal stability, puncture resistance and excellent wettability to the electrolyte, and does not require secondary processing of the base membrane, thereby reducing production time and production costs. Moreover, the isolation membrane has better uniformity than the sprayed ceramic layer, better electrolyte penetration, and stronger puncture resistance. Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.

[0133] In some embodiments, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and the above-mentioned separator.

[0134] In this embodiment, the specific materials and structures of the current collector and active material layer in the positive electrode sheet and the negative electrode sheet are not limited, and the positive electrode sheet and negative electrode sheet structures and components known in the art that can be used for secondary batteries can be selected.

[0135] The electrolyte that can be used in the embodiments of the present application can be an electrolyte known in the prior art. The specific type and structure of the electrolyte can be an electrolyte type that can be used in a secondary battery that is well known in the art, such as an ester electrolyte or an ether electrolyte, etc., which is not limited and will not be repeated here.

[0136] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0137] Example 1

[0138] 1. Preparation of isolation film

[0139] Alumina and boehmite are initially mixed in a mass ratio of 1:1, and then sintered in a muffle furnace at a temperature of 700°C for 1 hour. After mixing, the mixture is cooled and finally crushed to obtain a ceramic powder blend, that is, an inorganic ceramic material.

[0140] According to the mass percentage, 40 parts of PP, 30 parts of inorganic ceramic material, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation membrane.

[0141] 2. Preparation of electrolyte

[0142] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain a mixed organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent in a ratio of 1.2 mol / L to prepare an electrolyte.

[0143] 3. Preparation of positive electrode

[0144] The positive electrode active material lithium iron phosphate (LFP), the conductive agent conductive carbon black (SP) and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97.8:0.5:1.7 to obtain a mixed material, and the mixed material was fully stirred in N-methylpyrrolidone (NMP) to obtain a positive electrode active slurry of the corresponding positive electrode sheet, and the positive electrode active slurry was coated on an aluminum foil with a thickness of 13 μm, and the coating weight was 0.332 g / 1540.25 mm 2 , dried to obtain a positive electrode sheet with a porosity of 37%.

[0145] 4. Preparation of negative electrode

[0146] The negative electrode active material graphite, the conductive agent conductive carbon black (SP) and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97.6:1.0:1.4 to obtain a mixed material, and the mixed material was fully stirred in deionized water to obtain a negative electrode active slurry of the corresponding negative electrode sheet, and the negative electrode active slurry was coated on a copper foil with a thickness of 8 μm, and the coating weight was 0.154 g / 1540.25 mm 2 , dried to obtain a negative electrode sheet with a porosity of 35%.

[0147] 5. Preparation of Lithium-ion Batteries

[0148] The positive electrode sheet and the negative electrode sheet are rolled and cut respectively; then the negative electrode sheet, the separator and the positive electrode sheet are arranged in sequence, and winding is selected as the assembly method. After drying, electrolyte injection, packaging, formation, capacity division and other processes, a lithium-ion battery is obtained.

[0149] Example 2

[0150] Embodiment 2 is basically the same as Embodiment 1, and the main difference is:

[0151] In <Preparation of Isolation Membrane>, alumina and boehmite are initially mixed at a mass ratio of 1:1.5, and then sintered in a muffle furnace at a temperature of 700°C for 1 hour. After mixing, the mixture is cooled and finally crushed to obtain a ceramic powder blend, that is, an inorganic ceramic material.

[0152] The rest are the same as in Example 1.

[0153] Example 3

[0154] Embodiment 3 is basically the same as Embodiment 1, and the main difference is:

[0155] In <Preparation of Isolation Membrane>, alumina and boehmite are initially mixed in a mass ratio of 1:2, and then sintered in a muffle furnace at a temperature of 700°C for 1 hour. After mixing, the mixture is cooled and finally crushed to obtain a ceramic powder blend, that is, an inorganic ceramic material.

[0156] The rest are the same as in Example 1.

[0157] Example 4

[0158] Embodiment 4 is basically the same as Embodiment 1, and the main difference is:

[0159] In <Preparation of Isolation Film>, 45 parts of PP, 25 parts of inorganic ceramic materials, 3.5 parts of PS, 1.5 parts of CMC (thickener), 1 part of ammonium polyacrylate (dispersant), 3 parts of DBP (plasticizer), 1 part of AES (surfactant), 5.5 parts of SiO2 (nano oxide), 6 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass.

[0160] The rest are the same as in Example 1.

[0161] Example 5

[0162] Embodiment 5 is basically the same as Embodiment 1, and the main difference is:

[0163] In <Preparation of Isolation Film>, 50 parts of PP, 20 parts of inorganic ceramic material, 5 parts of PS, 2 parts of CMC (thickener), 3 parts of ammonium polyacrylate (dispersant), 4 parts of DBP (plasticizer), 3 parts of AES (surfactant), 6 parts of SiO2 (nano oxide), 7 parts of acetone (solvent) and 3 parts of deionized water were mixed evenly according to mass.

[0164] The rest are the same as in Example 1.

[0165] Example 6

[0166] Embodiment 6 is basically the same as Embodiment 1, and the main difference is:

[0167] In <Preparation of Isolation Film>, 40 parts of PE, 30 parts of inorganic ceramic material, 2 parts of PS, 1.5 parts of polyethylene glycol (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of BBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to their mass parts.

[0168] The rest are the same as in Example 1.

[0169] Example 7

[0170] Embodiment 7 is basically the same as Embodiment 1, and the main difference is:

[0171] In <Preparation of Isolation Film>, 40 parts of PE, 30 parts of inorganic ceramic material, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DEHP (plasticizer), 2 parts of polyoxyethylene fatty acid ester (surfactant), 5 parts of nano zinc oxide (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to parts by mass.

[0172] The rest are the same as in Example 1.

[0173] Example 8

[0174] Embodiment 8 is basically the same as Embodiment 1, and the main difference is:

[0175] In <Preparation of Isolation Film>, the slurry was sheared for 5 hours at a speed of 10,000 rpm using a high shear emulsifier to make the viscosity of the slurry reach 1,500 mPa.s (detected using a viscometer); then, the slurry was poured onto a small coater and a PP membrane with a thickness of 40 μm was cast on a glass sheet. The speed regulator frequency of the coater was set to 40 Hz.

[0176] The rest are the same as in Example 1.

[0177] Example 9

[0178] Embodiment 9 is basically the same as Embodiment 1, and the main difference is:

[0179] In <Preparation of Isolation Film>, the slurry was sheared for 4 hours at a speed of 5000 rpm using a high shear emulsifier to make the viscosity of the slurry reach 1200 mPa.s (detected using a viscometer); then, the slurry was poured onto a small coater and a PP membrane with a thickness of 25 μm was cast on a glass sheet. The speed regulator frequency of the coater was set to 20 Hz.

[0180] The rest are the same as in Example 1.

[0181] Comparative Example 1

[0182] Comparative Example 1 is substantially the same as Example 1, except that:

[0183] In <Preparation of Isolation Film>, 40 parts of PP, 30 parts of alumina, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass parts, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation film.

[0184] Compared with Example 1, Comparative Example 1 omits boehmite, that is, the inorganic ceramic material of Comparative Example 1 is only alumina.

[0185] Comparative Example 2

[0186] Comparative Example 2 is substantially the same as Example 1, except that:

[0187] In <Preparation of Isolation Film>, 40 parts of PP, 30 parts of boehmite, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass parts, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation film.

[0188] Compared with Example 1, Comparative Example 2 omits alumina, that is, the inorganic ceramic material of Comparative Example 2 is only boehmite.

[0189] Comparative Example 3

[0190] Comparative Example 3 is substantially the same as Example 1, except that:

[0191] In <Preparation of Isolation Film>, 40 parts of PP, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass parts, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain a diaphragm base film.

[0192] Then, the ceramic solution was sprayed onto the prepared diaphragm base film using a sprayer, with a ceramic coating of 3 μm thickness on both sides. The viscosity of the ceramic solution was 110±20 mPa·s, and the test was performed using a 62# rotor at 40 rpm.

[0193] Compared with Example 1, in Comparative Example 3, the ceramic coating is coated on the base film by spraying.

[0194] Comparative Example 4

[0195] Comparative Example 4 is substantially the same as Example 1, except that:

[0196] In <Preparation of Isolation Film>, 40 parts of PP, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass parts, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation film.

[0197] Comparative Example 4 Compared with Example 1, the inorganic ceramic material is omitted in Comparative Example 4.

[0198] Comparative Example 5

[0199] Comparative Example 5 is substantially the same as Example 1, except that:

[0200] In <Preparation of Isolation Film>, 40 parts of PP, 30 parts of inorganic ceramic material, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass parts, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation film.

[0201] Comparative Example 5 Compared with Example 1, PS (the second polymer) is omitted in Comparative Example 5.

[0202] Comparative Example 6

[0203] Comparative Example 6 is substantially the same as Example 1, except that:

[0204] In <Preparation of Isolation Film>, 40 parts of PP, 30 parts of inorganic ceramic material, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass parts, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation film.

[0205] Comparative Example 6 Compared with Example 1, the ammonium polyacrylate (dispersant) was omitted in Comparative Example 6.

[0206] Comparative Example 7

[0207] Comparative Example 7 is substantially the same as Example 1, except that:

[0208] In <Preparation of Isolation Film>, 40 parts of PP, 30 parts of inorganic ceramic material, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 2 parts of AES (surfactant), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly according to mass parts, and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by viscometer); then, the slurry was poured on a small coating machine, and a PP diaphragm with a thickness of 30μm was cast on a glass sheet, and the speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation film.

[0209] Comparative Example 7 Compared with Example 1, Comparative Example 7 omits SiO2 (nano oxide).

[0210] Comparative Example 8

[0211] Comparative Example 8 is substantially the same as Example 1, except that:

[0212] In <Preparation of Isolation Film>, 40 parts of PP, 30 parts of inorganic ceramic material, 2 parts of PS, 1.5 parts of CMC (thickener), 2 parts of ammonium polyacrylate (dispersant), 2 parts of DBP (plasticizer), 5 parts of SiO2 (nano oxide), 5 parts of acetone (solvent) and 2 parts of deionized water were mixed evenly by weight and stirred with a stirrer for 3 hours to make the slurry components evenly mixed; the mixture slurry was melted at 300°C for 1 hour, and then sheared with a laboratory high shear emulsifier for 4 hours at a speed of 8000rmp to make the slurry viscosity reach 1300mPa.s (detected by a viscometer); then, the slurry was poured on a small coating machine and a PP diaphragm with a thickness of 30μm was cast on a glass sheet. The speed regulator frequency of the coating machine was set to 30Hz. The cast diaphragm was placed in the drying chamber of the small coating machine for drying at a drying temperature of 90°C to obtain an isolation film.

[0213] Comparative Example 8 Compared with Example 1, AES (surfactant) was omitted in Comparative Example 8.

[0214] Performance Testing

[0215] 1. Test of isolation film

[0216] The isolation films prepared in the above-mentioned embodiments and comparative examples were subjected to a liquid absorption test, an ionic conductivity test, a thermal shrinkage test, and a mechanical strength (puncture strength) test.

[0217] (1) Liquid absorption test method: Take a 5×5cm piece from each group 2 The separator is weighed and recorded as a. The separator is placed in the electrolyte and soaked for 1 hour to fully absorb the electrolyte. After the absorption is completed, the separator is hung for 5 minutes to dry the electrolyte attached to the surface of the separator, and the weight is recorded as b. The liquid absorption rate of the separator is (ba) / a×100%.

[0218] (2) Test method for ionic conductivity test: The solution resistance RL is measured by the AC impedance method (in fact, RL includes all ohmic resistances in the system, such as the high-resistance film on the electrode surface, the ohmic resistance of the diaphragm and the ohmic resistance of the electrode itself, but in this application, the diaphragm resistance is the main part of the solution resistance, so it is approximately considered that the isolation membrane resistance Rm = RL); the isolation membrane thickness d is measured by a screw micrometer, and S is used to represent the area of ​​the electrode, and the area S of the electrode is always 1 cm 2 (The electrode is a 1×1 cm stainless steel sheet); then, the ionic conductivity к can be calculated by the following formula: к=d / (RL·S).

[0219] (3) Test method for heat shrinkage rate: stack the isolation film into 3 layers, flatten them, exhaust the air between the films, take out the cutting plate (300*100), cut out the isolation film sample, measure the length A1 and width B1 of the cut sample, set the oven temperature to 130°C, and keep it warm for 10 minutes after the temperature is reached; put the isolation film sample into the oven and time it for 10 minutes; after the time is up, take out the isolation film, cool it for 10 minutes, and measure the length A2 and width B2 of the isolation film sample. Then, the longitudinal heat shrinkage of the isolation film A = (A1-A2) / A1*100%; the transverse heat shrinkage of the isolation film B = (B1-B2) / B1*100%.

[0220] Then, the thermal shrinkage of the separator is the average value of the above-mentioned longitudinal thermal shrinkage and transverse thermal shrinkage.

[0221] (4) Puncture strength test method: Use a diaphragm puncture test machine to cut the diaphragm into strips. The width of the strip must be greater than 100 mm. Install a test piece with a width of 100 mm on the membrane fixing clamp ring, and then use a steel needle with a diameter of 1 mm and a radius of 0.5 mm at the top of the diameter to puncture at a speed of 50 mm / min, and read the load of the steel needle penetrating the test piece.

[0222] The test results are shown in Table 1 below.

[0223] Table 1 Performance test results of the isolation membranes of various embodiments and comparative examples

[0224]

[0225]

[0226] From the data in Table 1, it can be seen that compared with the isolation membranes of Comparative Examples 1-8, the isolation membranes provided by Examples 1-9 of the present invention have a certain degree of improvement in liquid absorption rate, ionic conductivity, thermal shrinkage, and puncture strength. In particular, Example 1 (or Example 2) of the present invention shows a better technical effect. Compared with Comparative Examples 1-8, the isolation membrane prepared by Example 1 has a significant improvement in liquid absorption rate, ionic conductivity, thermal shrinkage, puncture strength, etc.

[0227] In addition, by comparing the analysis of Example 1 with Comparative Examples 1 and 2, it can be seen that when alumina and boehmite are used as inorganic ceramic materials, the performance of the prepared isolation membrane is better than that of alumina or boehmite alone. Further, by comparing the analysis of Example 1 with other examples or comparative examples, it can be seen that when alumina and boehmite are mixed in a mass ratio of 1:1 and added to the slurry, the physical and electrochemical properties of the cast isolation membrane are better.

[0228] Through the analysis and comparison of Example 1 and Comparative Example 3, it can be seen that compared with Comparative Example 3 which adopts the existing coating method to prepare the ceramic coating on the surface of the base film, the embodiment of the present invention directly adds ceramic powder into the PP diaphragm production process, so that the prepared isolation membrane shows better usability in both the diaphragm performance test and the subsequent electrical performance test.

[0229] By comparing Example 1 with Comparative Examples 4-8, it can be seen that if any one of the components such as the second polymer, inorganic ceramic material, dispersant, surfactant, nano-oxide, etc. is omitted, the performance of the isolation membrane obtained will be reduced. This shows that the first polymer, the second polymer, the inorganic ceramic material, the thickener, the dispersant, the plasticizer, the surfactant and the nano-oxide in the isolation membrane of the present invention play a synergistic role, and synergistically improve the physical and electrochemical properties of the isolation membrane, especially improve the thermal stability, puncture resistance and wettability of the isolation membrane to the electrolyte. In addition, it can be seen from the above Comparative Examples 4-8 that the isolation membrane obtained by combining SiO2 and PS has better physical and electrochemical properties than SiO2 alone.

[0230] 2. Testing of lithium-ion batteries

[0231] The lithium-ion batteries obtained from the above-mentioned embodiments and comparative examples were subjected to cycle capacity retention test, heating test and overcharge test.

[0232] (1) Cycle capacity retention rate test method: Using an electrochemical charge and discharge cabinet, at 25°C, charge the battery cell at a constant current of 2C to an upper cut-off voltage of 3.65V, and then charge at a constant voltage of 3.65V to a current of 0.05C; after standing for 30 minutes, discharge the battery cell at a constant current of 1C to 2.0V, record the discharge capacity of the first cycle, repeat the above steps for 300 cycles, and record the discharge capacity of the 300th cycle; then, the cycle capacity retention rate of 300 cycles = discharge capacity of the 300th cycle / discharge capacity of the first cycle*100%.

[0233] (2) Heating test: Tested in accordance with DB34 / T3377-2019 standard.

[0234] (3) Overcharge test: Tested in accordance with GB / T31485-2015 standard.

[0235] The test results are shown in Table 2 below.

[0236] Table 2 Battery performance test results of various embodiments and comparative examples

[0237]

[0238] It can be seen from the data in Table 2 that, compared with the isolation membranes of comparative examples 1-8, the batteries made using the isolation membranes provided by embodiments 1-9 of the present invention have improved battery cycle performance; in addition, the heating test also shows that the embodiments of the present invention improve the short-circuit temperature, and the overcharge test shows that the embodiments of the present invention reduce the temperature rise, which indicates that the isolation membranes of the embodiments of the present invention have better thermal stability and improve the safety performance of the battery.

[0239] In summary, the separator provided by the present invention has good thermal stability, puncture resistance and excellent wettability to the electrolyte, and does not require secondary processing of the base film, thereby reducing production time and production costs. At the same time, the separator has better uniformity than the sprayed ceramic layer, better electrolyte penetration effect, and stronger puncture resistance, thereby improving the cycle performance and safety performance of using the separator.

[0240] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0241] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0242] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0243] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0244] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A separation film, characterized in that: The isolation film comprises the following components: A first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and nano-oxides; Wherein, the first polymer comprises polypropylene and / or polyethylene; The second polymer includes polystyrene.

2. The isolation film according to claim 1, characterized in that: The isolation film comprises the following components in parts by weight: 40-50 parts of the first polymer, 2-5 parts of the second polymer, 20-30 parts of the inorganic ceramic material, 5-6 parts of the nano oxide, 1-2 parts of the thickener, 1-3 parts of the dispersant, 2-4 parts of the plasticizer and 1-3 parts of the surfactant.

3. The isolation membrane according to claim 1 or 2, characterized in that: The thickening agent includes polyethylene glycol and / or carboxymethyl cellulose.

4. The isolation membrane according to claim 1 or 2, characterized in that: The inorganic ceramic material includes alumina and boehmite; Optionally, the mass ratio of alumina to boehmite is 1:(0.5-3).

5. The isolation film according to claim 1 or 2, characterized in that: The dispersant includes a polyacrylate ammonium salt dispersant or a modified polyacrylate ammonium salt dispersant; And / or, the plasticizer includes a phthalate compound, and the phthalate compound includes at least one of DBP, BBP, DEHP, DNOP, DIDP or DINP; And / or, the surfactant includes at least one of sodium polyoxyethylene fatty alcohol ether sulfate, polyoxyethylene fatty acid ester, dodecyl methyl betaine, sodium dodecyl benzene sulfonate or sodium dodecyl sulfate; And / or, the nano-oxide includes at least one of nano-silicon oxide, nano-zinc oxide or nano-titanium oxide.

6. The isolation membrane according to claim 1 or 2, characterized in that: The isolation film further comprises a pore-forming agent, and the pore-forming agent comprises white oil; Optionally, the mass fraction of the pore-forming agent is 0.01 to 1 part; And / or, the isolation film further comprises an antioxidant, and the antioxidant comprises 2,6-di-tert-butyl-p-cresol; Optionally, the antioxidant is present in an amount of 0.01 to 1 part by weight; And / or, the isolation film has a thickness of 5 μm to 35 μm.

7. A method for preparing an isolation film, characterized in that: The steps include: Mixing a first polymer, a second polymer, an inorganic ceramic material, a thickener, a dispersant, a plasticizer, a surfactant and a nano-oxide to obtain a mixture; wherein the first polymer includes polypropylene and / or polyethylene; and the second polymer includes polystyrene; The mixture is sequentially melted, stirred and sheared to obtain a slurry; The slurry is coated on a substrate, dried, and separated from the substrate to obtain the isolation film.

8. The method for preparing the isolation film according to claim 7, characterized in that: The melting temperature is 300°C to 400°C, and the melting time is 1h to 2h; And / or, the stirring time is 2h to 3h; And / or, the shearing speed is 1000-14000 rpm, and the shearing time is 4h-5h.

9. The method for preparing an isolation film according to claim 7 or 8, characterized in that: The viscosity of the slurry is 1200-1500 mPa.s; And / or, the coating is performed using a coating machine, and the speed regulator frequency of the coating machine is set to 20 to 40 Hz; And / or, the drying temperature is 70°C to 90°C; And / or, the thickness of the isolation film is 25 μm to 35 μm; Optionally, the mixture further includes a pore-forming agent; Optionally, the mixture also includes an antioxidant.

10. A battery, characterized in that: The battery comprises the separator according to any one of claims 1 to 6 or the separator prepared by the method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Production and use of ceramic composite materials based on a polymeric carrier film

    CN102414869A

  • Making a lithium ion battery separator

    US20130131200A1

  • Electrochemical device, new non-woven fabric ceramic separator, and preparation method therefor

    WO2022068178A1

Cited By

  • Composite material, preparation method thereof and refrigerator

    CN121427261A